Wolves - Schuh, Mari C., 1975- (2020)
"With their eerie howls and fierce hunting skills, wolves are fascinating creatures. These loyal pack animals are close relatives to man's best friend, dogs. Learn more about these proud hunters"--
Includes index.
Ages 6-8
Grades 2-3
Keywords: Wolves -- Juvenile literature